Epigenetic Inactivation of KLF4 is Associated with Urothelial Cancer Progression and Early Recurrence - Li, Heng; Wang, Ji; Xiao, Wei; Xia, Ding; Lang, Bin; Wang, Tao; Guo, Xiaolin; Hu, Zhiquan; Ye, Zhangqun; Xu, Hua (The Journal of urology, 2014)
Purpose KLF4 is a transcription factor with divergent functions in different malignancies. We analyzed KLF4 expression and DNA methylation, and their clinical relevance and biological function in urothelial cancer. Materials and Methods Immunohistochemistry and Sequenom™ MassARRAY® were done to detect the expression and promoter methylation of KLF4 in urothelial cancer tissues. The association of the recurrence-free survival rate and decreased KLF4 or KLF4 methylation status was analyzed by the Kaplan-Meier method, Cox regression analysis and ROC assay. Lentivirus based KLF4 over expression and dsRNA mediated knockdown were used to detect KLF4 functions in urothelial cancer in vitro and in vivo. Results KLF4 was down-regulated in urothelial cancer due to promoter hypermethylation. Each correlated with recurrence-free survival in patients with nonmuscle invasive bladder cancer after transurethral resection of bladder cancer, which potentiates them as valuable predictive biomarkers for early recurrence. Moreover, in and ex vivo experiments showed that KLF4 suppressed urothelial cancer cell growth, migration and invasion inhibited the epithelial-to-mesenchymal transition. Conclusions KLF4 may function as a tumor suppressor gene in urothelial cancer since down-regulation of KLF4 by promoter hypermethylation would promote cancer progression. In addition, decreased expression of KLF4 or its promoter hypermethylation may have predictive value for early recurrence in patients with nonmuscle invasive bladder cancer.